Peningkatan Akurasi Konsentrasi Pemberian Pupuk Pada Sistem Hidroponik Menggunakan Programmable Logic Controller - Ali Sadiyoko; Kevin Adi Perdana; Christian Fredy Naa (TEKNIK, 2023)
Hydroponics is a farming method using water as a medium for storing nutrients (fertilizer/nutrients). Therefore, the concentration of dissolved fertilizers in the water is crucial for plant growth. The method of measuring dissolved fertilizers in hydroponic systems is usually done by measuring the value of the EC and Total Dissolved Solids of the solution. However, because the EC and TDS measurement processes are not carried out continuously, this can result in plant growth being disrupted. In this study, an automatic fertilizer concentration control system was designed based on EC values that can be monitored continuously. The fertilizer concentration control process will be carried out automatically using a PLC, which is equipped with a TDS sensor and several pumps. EC value measurements are carried out indirectly using a TDS sensor. Testing of the design system was carried out for 8 days, during which time the design of this system managed to maintain EC values between 0.844 mS/cm to 1.051 mS/cm. The standard EC value required by lettuce plants is 0.8 mS/cm ~ 1.2 mS/cm. This shows that this system is more accurate than the reference system, which is able to maintain EC values between 0.8 mS/cm to 1.2 mS/cm.